mTOR pathway as a potential therapeutic target for cancer stem cells in canine mammary carcinoma - Michishita, Masaki; Ochiai, Kazuhiko; Nakahira, Rei; Azakami, Daigo; Machida, Yukino; Nagashima, Tomokazu; Nakagawa, Takayuki; Ishiwata, Toshiyuki (Frontiers in Oncology, 2023)
Mammary adenocarcinoma, the most common cancer in female dogs, often exhibits distinct the lymph node and lung metastases and has a higher mortality rate. However, mammary adenocarcinoma has no established treatment, except early surgical excision. Canine mammary carcinoma has many common features with human mammary carcinoma, including clinical characteristics, heterogeneity, and genetic aberrations, making it an excellent spontaneous tumor model for human breast cancer. Diverse cancers comprised heterogeneous cell populations originating from cancer stem cells (CSCs) with self-renewal ability. Therefore, in addition to conventional therapy, therapeutic strategies targeting CSCs are essential for cancer eradication. The present study aimed to extract inhibitors of canine mammary CSCs that suppress their self-renewal ability. Sphere-formation assay, which evaluates self-renewal ability, was performed for the canine mammary cancer cell lines CTBp and CNMp. The spheres formed in this assay were used in inhibitor library screening, which identified various signaling pathways such as proteosome, stress inducer, and mammalian target of rapamycin (mTOR). The present study focused on the mTOR signaling pathway. Western blotting showed higher levels of phosphorylated mTOR in sphere-forming CTBp and CNMp cells than in adherent cells. Drug sensitivity examination using the mTOR inhibitors everolimus and temsirolimus, the revealed dose-dependent reductions in viability among both sphere-forming cells and adherent cells. In mice transplanted with CTBp-derived spheres, everolimus treatment significantly decreased tumor volume compared to control. These results reveal that the mTOR signaling pathway may be a potential to be a therapeutic target in both cancer cells and CSCs. Novel therapeutic strategies for canine mammary carcinoma are expected to benefit to human breast carcinoma as well.